2007
DOI: 10.1097/qad.0b013e32805e8711
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary counselling and testing: uptake, impact on sexual behaviour, and HIV incidence in a rural Zimbabwean cohort

Abstract: Motivation for VCT uptake was driven by knowledge and education rather than sexual risk. Increased sexual risk following receipt of a negative result may be a serious unintended consequence of VCT. It should be minimized with appropriate pre- and post-test counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
159
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(191 citation statements)
references
References 27 publications
26
159
4
Order By: Relevance
“…21 People with higher education may have better access to health care services generally, and particularly more uptake of antenatal care among females with higher education. 48 Wealth may make it easy to afford payment of transport to go to testing centres consultation fees since health care services are paid for in Zimbabwe. 49 The results observed here show increased odds of having been tested for HIV among the wealthier than the poorer for males, and no association between wealth and HIV testing for females after controlling for community wealth/poverty.…”
Section: Key Findingsmentioning
confidence: 99%
“…21 People with higher education may have better access to health care services generally, and particularly more uptake of antenatal care among females with higher education. 48 Wealth may make it easy to afford payment of transport to go to testing centres consultation fees since health care services are paid for in Zimbabwe. 49 The results observed here show increased odds of having been tested for HIV among the wealthier than the poorer for males, and no association between wealth and HIV testing for females after controlling for community wealth/poverty.…”
Section: Key Findingsmentioning
confidence: 99%
“…However, similar effects are not as convincing for the large proportion who test negative. A recent study found increased risk behaviors in HIV negative individuals after undergoing VCT (Sherr et al 2007) while a comparison of two VCT strategies in Zimbabwe found that despite improved acceptability of the trial VCT strategy, risk behaviors continued in individuals testing negative following their diagnosis (Corbett et al 2007). Although there has been a focus on increasing the number of people undergoing HIV testing and counseling, currently less than a quarter of HIV positive individuals in most countries in sub-Saharan Africa are aware of their status (WHO, UNAIDS and UNICEF 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of HIV counselling and testing is critical in ensuring the potential impact of risk reduction (Sherr et al 2007). The current pre-dominant counselling models such as the Egan model in South Africa and the TASO model in Uganda are seen as less structured to effect any behavioural change compared to the risk reduction model used in many other parts of the world (Van Rooyen et al 2010).…”
Section: Introductionmentioning
confidence: 99%